Implementation of Zakat in Chili Agriculture From The Perspective of Yusuf Al-Qardhawi: A Case Study Lima Puluh District, Batu Bara Regency - Asroful Anwar (AT-TAFAHUM: Journal of Law, 2017)
This study examines the implementation of agricultural zakat on chili farming in Lubuk Cuik, Bulan-Bulan, and Titi Merah Villages, Batu Bara Regency, and analyzes its conformity with the zakat theory proposed by Yusuf Al-Qardhawi. The research employed a qualitative approach through field research and interviews with farmers, religious leaders, and community members. The findings reveal that community understanding of chili agricultural zakat remains diverse. Some respondents consider chili crops subject to agricultural zakat because they have economic value and generate income, while others argue that chili is not included among staple food commodities and therefore is not subject to agricultural zakat. The study found several practices consistent with Yusuf Al-Qardhawi’s opinion, particularly regarding the obligation to pay zakat on agricultural products with economic value and the deduction of production costs before calculating zakat. However, significant discrepancies were also identified. Most farmers do not consider the nisab requirement, apply a zakat rate of 2.5% instead of the prescribed 5% or 10%, and in some villages calculate zakat based on gross income rather than net income after deducting production costs. Furthermore, zakat distribution is generally conducted directly by farmers to needy individuals, while institutional zakat management remains limited due to insufficient public awareness and trust in formal zakat institutions. The study concludes that the implementation of chili agricultural zakat in the research area has not fully conformed to Yusuf Al-Qardhawi’s perspective, primarily due to limited public understanding of zakat regulations, nisab requirements, and calculation methods.